2004
DOI: 10.1007/s00449-004-0357-1
|View full text |Cite
|
Sign up to set email alerts
|

Linearized kinetic model of Listeria monocytogenes biofilm growth

Abstract: In this study the dynamics of biofilm formation on aluminum has been investigated. The process of cell growth has been observed using fluorescence microscopy. It has been confirmed that the process of biofilm formation can be represented as a sum of two separate processes: cell adhesion and colony proliferation. The derived set of equations describes kinetics of surface population growth and characteristic times for adsorption and combined growth processes, including characteristic time for the nutrient supply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
(13 reference statements)
0
8
0
2
Order By: Relevance
“…Takhistov and George (2004) observed rapid adherence (within 3-5 sec) of a few L. monocytogenes cells to random areas on an aluminium surface. This adherence was initially sparse and uniform but became more clustered over time, eventually leading to the formation of microcolonies.…”
Section: Initiationmentioning
confidence: 98%
See 2 more Smart Citations
“…Takhistov and George (2004) observed rapid adherence (within 3-5 sec) of a few L. monocytogenes cells to random areas on an aluminium surface. This adherence was initially sparse and uniform but became more clustered over time, eventually leading to the formation of microcolonies.…”
Section: Initiationmentioning
confidence: 98%
“…Takhistov and George (2004) observed that following the initial attachment of L. monocytogenes, new Biofilms in the Food Environment cells preferentially attach to the extracellular polymeric substances (EPS) produced by the initial adherent cells. They also noted that daughter cells did not detach from the parent cells but instead formed microcolonies, growing toward areas of higher nutrients and fewer cells.…”
Section: Development Maturation and Detachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Em geral, a diferença entre a simples adesão do micro-organismo às superfícies e o biofilme pode ser definida através dos seguintes critérios: o papel da superfície no crescimento da população bacteriana e a existência de comunicação célula-a-célula (quorum sensing) dentro da população. 12 Enquanto o termo biofilme se refere a um microambiente complexo em uma superfície, existem vários outros termos que se referem à adesão das bactérias às superfícies. Quando células planctônicas se associam a uma superfície, o termo usual é aderência.…”
Section: Biofilmesunclassified
“…10 Os biofilmes podem ser formados por populações desenvolvidas a partir de uma única, ou de múltiplas espécies, podendo ser encontrados em uma variedade de superfícies bióticas e/ou abióticas. 13 A adesão bacteriana pode gerar o processo de multiplicação microbiana e formação de biofilme [12][13][14] e pode ser afetado por uma série de fatores como a espécie do micro-organismo, as condições de crescimento e a produção de substâncias extracelulares poliméricas (EPS).…”
Section: Adesão E Formação Do Biofilmeunclassified